Thomas Cromwell : a revolutionary life - MacCulloch, Diarmaid (New York, Viking, 2018)
Examines the life of King Henry VIII's right-hand man, who did everything he could to secure the future of a son he loved dearly, but who ultimately could not control the unpredictable monarch
Introduction -- Journeys. Ruffian ; The return of the native ; In the Cardinal's service: 1524-1528 ; Managing failure: 1528-1529 ; Serving two masters: 1530 -- New wine. Council and Parliament: 1531 ; New Year's gifts: 1532 ; Making a difference: 1532 ; A royal marriage: 1532-1533 -- Touching pitch. Treason in prospect: 1533-1534 ; Spirituals: 1534-1535 ; Deaths for religion: 1535 ; Progresses and scrutinies: 1535-1536 ; Surrenders and the scaffold: 1536 -- Power and its reward. Summer opportunities: 1536 ; Grace for the Commonwealth: 1536 ; The reckoning: 1537 ; The King's uncle?: 1537-1538 ; Cutting down trees: 1538 -- Nemesis. Shifting dynasties: 1538-1539 ; Stumbling blocks: 1539 ; Downfall: 1539-1540 ; Futures
Includes bibliographical references (pages 557-582) and index
Keywords: Cromwell, Thomas, -- Earl of Essex, -- 1485?-1540; Statesmen -- England -- Biography; Great Britain -- History -- Henry VIII, 1509-1547; Great Britain -- Politics and government -- 1509-1547; Great Britain -- Court and courtiers -- Biography; Biographies; Nonfiction